PSV-15 Genomic basis of reproductive performance in PRRSV-infected sows. (30th November 2020) - Hickmann, Felipe; Neto, José Braccini; Kramer, Luke; Gray, Kent; Huang, Yijian; Dekkers, Jack; Sanglard, Letícia P; Serão, Nick
Abstract: Previous studies have shown that reproductive traits in sows during porcine reproductive and respiratory syndrome (PRRS) outbreaks are lowly heritable. However, little is known about the genomic basis of reproductive performance in PRRS virus (PRRSV)-infected sows. Thus, the objective of this work was to evaluate the genomic basis of reproductive performance in PRRSV-infected sows. Farrowing data from 475 Duroc and 405 Landrace sows that experienced a PRRS outbreak were used. Heritability and genome-wide association studies (GWAS) based on 30K SNP genotypes were performed for each breed separately, for number of piglets born alive (NBA), stillborn piglets (NSB), mummified piglets (NM), piglets born dead (NBD; NSB+NM), total number of piglets born (TNB; NBA+NBD), and piglets weaned (NW). Heritabilities were estimated with ASReml using a model with the fixed-effect of parity and an animal random-effect, using a genomic-relationship matrix. GWAS was performed using Bayes-B in GenSel with a model fitting parity as fixed-effect and SNP effects as random. Heritability estimates (± standard error) for NBA, NSB, NM, NBD, TNB, and NW were 0.07±0.07, 0.02±0.11, 0.04±0.10, 0.08±0.08, 0.08±0.07, 0.06±0.04, respectively, for Duroc, and 0.09±0.07, 0.10±0.07, 0.10±0.08, 0.11±0.07, 0.07±0.08, 0.07±0.08, respectively, for Landrace. For Duroc, GWAS identified a quantitative trait locus (QTL) on chromosome (chr) 3 [114-120 megabases (Mb)] explaining 3.9% of the genetic variance (GV) for NBA, on chr 13 (189-193 Mb) explaining 2.7% GV for NBD, and on chr 5 (36-41 Mb) explaining 4.3% GV for TNB. For Landrace, GWAS identified a QTL on chr 13 (154-162 Mb) explaining 12.8% GV for NBA, on chr 14 (59-69 Mb) explaining 2.5% GV for NBD, and on chr 10 (7-9 Mb) explaining 4.1% GV for NW. These results indicate that reproductive traits are lowly heritable during a PRRS outbreak with few QTL identified in Duroc and Landrace sows.